Deformation mechanism of Ni54Mn25Ga20.9Gd0.1 high-temperature shape memory alloy. (December 2015) - Zhang, Xin; Sui, Jiehe; Cai, Wei; Liu, Qingsuo; Liu, Ailian
Abstract: Ni54 Mn25 Ga20.9 Gd0.1 polycrystalline high-temperature shape memory alloy displayed high compressive fracture strain of 24.6% and large shape memory effect of 7.5%. However, its deformation mechanism was still unknown. In this paper, the structure revolution characterized by XRD and TEM indicated a new deformation mechanism different before was found. The deformation process of Ni54 Mn25 Ga20.9 Gd0.1 alloy could be divided into four stages, including elastic deformation of non-modulated tetragonal martensite (T), stress-induced T to seven-layered modulated martensite (7 M) transformation, variants reorientation of 7 M, and elastic–plastic deformation of reoriented 7 M. The 7 M formed by compression deformation disappeared completely after heating to the temperature above A f . Highlights: The deformation mechanism of Ni54 Mn25 Ga20.9 Gd0.1 high-temperature shape memory alloy is investigated. A new stress-induced martensitic transformation of T → 7 M is observed. The deformation process of Ni54 Mn25 Ga20.9 Gd0.1 alloy includes elastic deformation, T → 7 M transformation, variants reorientation of 7 M, and elastic–plastic deformation.